A bio-inspired versatile free-standing membrane for oral cavity microenvironmental monitoring and remineralization to prevent dental caries. Issue 2 (23rd November 2022) - Cheng, Kai; She, Peng; Wang, Hong; Wang, Zengkai; Zhang, Liwei; Tang, Xu; Yuan, Liang; Feng, Yonghai; Song, Xiaolu; Pan, Guoqing; Yang, Juan; Liu, Lei
Abstract : The fast monitoring of oral bacterial infection, bacterial clearance and repairing of enamel damage caused by dental caries relies on an effective way of monitoring, killing and repairing in situ, but presents a major challenge in oral healthcare. Abstract : The fast monitoring of oral bacterial infection, bacterial clearance and repairing of enamel damage caused by dental caries relies on an effective way of monitoring, killing and repairing in situ, but presents a major challenge in oral healthcare. Herein, we developed a bio-inspired versatile free-standing membrane by filling TiO2 nanotube arrays with β-sheet-rich silk fibroin and cleaving them from Ti foil, as inspired by nacre or enamel-like structures. The robust transparent membrane exhibited good mechanical properties, and could indicate acid-base microenvironment variation and the infection of S. mutans in a 5 min test by loading cyanidin cations in the membrane. Meanwhile, it can be used for photocatalysis and nanoreservoirs ascribed to TiO2 nanotubes, to kill and remove 99% of S. mutans bacteria under interval UV irradiation with low-power density, and load functional peptide to induce the remineralization on the etched-enamel for long-term treatment, tested in vitro and in vivo . The mechanical property of repaired enamel is improved in comparison. This bio-inspired constructed membrane would be applied in the prevention and treatment of oral cavity related diseases, such as enamel demineralization and dental caries, etc.